2019
DOI: 10.3171/2017.9.jns171811
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of detecting enlargement of aneurysms using different MRI modalities and measurement protocols

Abstract: OBJECTIVE Aneurysm growth is considered predictive of future rupture of intracranial aneurysms. However, how accurately neuroradiologists can reliably detect incremental aneurysm growth using clinical MRI is still unknown. The purpose of this study was to assess the agreement rate of detecting aneurysm enlargement employing generally used MRI modalities. METHODS Three silicone flow phantom models, each with 8 aneurysms of various sizes at different sites, were used in this study. The aneurysm models were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The resolution (both in plane and in the slice direction) was around 0.5 mm, which was our detection limit for aneurysm growth. Previous studies showed that the detection rate for aneurysm growth was high for growth > 0.4 mm, 26 but smaller enlargement might be missed. Nevertheless, these smaller enlargements are also difficult to detect on other modalities and might have limited clinical relevance.…”
Section: Discussionmentioning
confidence: 96%
“…The resolution (both in plane and in the slice direction) was around 0.5 mm, which was our detection limit for aneurysm growth. Previous studies showed that the detection rate for aneurysm growth was high for growth > 0.4 mm, 26 but smaller enlargement might be missed. Nevertheless, these smaller enlargements are also difficult to detect on other modalities and might have limited clinical relevance.…”
Section: Discussionmentioning
confidence: 96%
“…Although, according to a phantom study on silicone models, the mean detection rates of MRA for an increase in aneurysmal dimensions were 95.7%, the mean detection rate for aneurysmal growth was only 54.8%. 31 As this would increase the incidence of inefficient scanning, the cost-effectiveness of frequent follow-up would be even lower. In addition, false positives would cause unnecessary stress for patients and may unnecessarily expose patients to treatment complications.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the intracranial aneurysm (IA), also known as the brain aneurysm, is a high-lethality-rate disease and high in proportion in the population. The growth and rupture of IAs are the result of multiple factors, such as the external environment, smoking, and so on. , The presence of IAs can accelerate growth and rupture of other surrounding IAs . Normally, stroke and neurological disease caused by IAs can give rise to 50% of patients dying before treatment .…”
mentioning
confidence: 99%
“…The growth and rupture of IAs are the result of multiple factors, such as the external environment, smoking, and so on. 1,2 The presence of IAs can accelerate growth and rupture of other surrounding IAs. 3 Normally, stroke and neurological disease caused by IAs can give rise to 50% of patients dying before treatment.…”
mentioning
confidence: 99%